A Review on Registration of Medical Images Using Graph Theoretic Approaches - Akshaya R; Hema P Menon (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Image registration is very essential for image analysis especially in the medical field. The registered image helps us to find a lot of things like the presence of a tumor, aneurysm, and many more. Image registration is a process of aligning two images that were captured during different conditions that makes analyzing of images possible. There are various methods in which images can be registered. This paper mainly discusses the methods that use the graph approach to register the medical images. The main focus is on rigid and non-rigid registration techniques and gives a brief description of the methods present.